2009
DOI: 10.20870/ijvr.2009.8.1.2712
|View full text |Cite
|
Sign up to set email alerts
|

On the Determinants of Size-Constancy in a Virtual Environment

Abstract: An important aspect of a subject�s perception of virtual objects in a virtual environment is whether the size of the object is perceived as it would be in the physical world, which is named size-constancy. The ability of subjects to appreciate size-constancy in an immersive virtual environment was studied while scene complexity, stereovision and motion parallax visual factors were manipulated resulting in twelve different viewing conditions. Under each visual condition, 18 subjects made size judgments of a vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Based on the results, it can be said that our RQ was answered. Similar to previous studies reported in the literature [ 32 , 33 , 34 ], we also highlight the fact that providing binocular disparity is important when estimating distances. Its existence can change an overestimation to an underestimation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Based on the results, it can be said that our RQ was answered. Similar to previous studies reported in the literature [ 32 , 33 , 34 ], we also highlight the fact that providing binocular disparity is important when estimating distances. Its existence can change an overestimation to an underestimation.…”
Section: Discussionsupporting
confidence: 89%
“…As can be suspected, the composition of VEs can also affect distance estimation [ 28 , 29 ], although usually underestimations occur in them [ 30 , 31 ]. Multiple studies mention the importance of binocular disparity regarding distance estimation [ 32 , 33 , 34 ]. According to Vaziri et al, realism plays an important role in the estimation process [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…(ii) Motion parallax [113] concludes that 'there is no empirical evidence that providing motion parallax improves distance perception in virtual environments' and [114][115][116][117][118] find very little benefit from motion of the observer.…”
Section: (I) Accommodationmentioning
confidence: 99%
“…Although binocular disparity is considered to be a highly effective depth cue (Cutting & Vishton, 1995), its relevance is limited to relatively close distances, with the effect diminishing with increasing distance (Cutting & Vishton, 1995; Foley, 1991; Lappin, 2014; Nagata, 1989; Palmisano et al., 2010). Studies that investigated tasks involving spatial judgment came to varying conclusions when stereoscopic viewing conditions were compared to monoscopic ones: Tasks in close proximity to the participant (< 2 m) benefitted from the availability of stereoscopic depth information (Bingham et al., 2001; Luo et al., 2009; van der Kamp et al., 1997), while tasks in which had to be focused on somewhat farther distances did not show an advantage of stereoscopic conditions over monoscopic ones (Creem-Regehr et al., 2005; Eggleston et al., 1996; Roumes et al., 2001; Willemsen et al., 2008). Participants in our study saw the virtual environment stereoscopically.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Depth information retrieved from motion parallax requires real-time tracking of the user’s translational movements. A full-body motion-capture system was implemented in our study, even though several studies suggest that motion parallax is not crucial for accurately completing tasks relating to distance judgments (Jones et al., 2008; Luo et al., 2009; Narayan et al., 2005). The ability to move freely in the virtual environment affects, however, immersion and by that the user’s experience of presence, which has been shown to affect user performance (see Bowman & McMahan, 2007; Creem-Regehr et al., 2015; Cummings & Bailenson, 2014; Hendrix & Barfield, 1995; Schuemie et al., 2001; Slater & Wilbur, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%